Strategi Pengelolaan Pantai Baron Sebagai Pariwisata Berkelanjutan Dalam Menyongsong Abad Samudra Hindia - Kiswantoro, Amin; Susanto, Dwiyono Rudi (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2020)
Baron Beach is one of the beaches in Yogyakarta which is directly adjacent to the Indian Ocean. This beach has potential resources that can be developed into sustainable tourism. This article discusses the strategy of processing the existing resources on Baron Beach to become sustainable tourism in welcoming the Indian Ocean Century. The research was conducted using a descriptive method with a qualitative approach. Data collection was carried out by observation and interviews. Data processing was performed by using Triagulation analysis techniques and SWOT analysis. Several strategies that can be applied in developing Baron Beach into sustainable tourism include; (1) Developing Of disability-friendly tourism facilities and culinary-based marine tourism; (2) Establishing a fishermen education tourism center in Gunungkidul; (3) Organizing national and international culinary events; (4) Add eco-friendly tourist attractions; (5) Conducting comparative studies on tourism management in a professional manner which also develops effective and sustainable tourism products, partnership patterns and community empowerment. Keywords: Baron; Century; Indian; Ocean; SWOT